Positively Izzy - Libenson, Terri (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2018)
Tells the intersecting stories of dreamer Izzy, who has trouble focusing on schoolwork, and Brainy Bri, who wants people to think of her as more than a brainiac.
Booklist
Horn Book
School Library Journal
Booklist, March 2018
Horn Book, November 2018
Kirkus Review, March 2018
Keywords: Girls -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Girls -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Girls -- Fiction; Middle schools -- Fiction; School stories